Pengembangan Media Video Pembelajaran Tema 6 Subtema 2 Untuk Siswa Kelas SD Negeri 17 Pasar Masurai 1 - Gingga Prananda; Ali Wardana; Yulia Darniyanti (Jurnal Dharma PGSD, 2021)
Abstract: The implementation of Thematic learning at SD Country 17 Pasar Maurai I is not yet optimal. That is because teachers only use books in learning, so students are less enthusiastic in following the learning process. The use of video media in Thematic learning can provide an alternative way for students to motivate students to study harder. The formulation of the problem in this research is how the development, feasibility, and effectiveness and practicality of learning video media Theme 6 Subtheme 2 for Grade IV Students. The purpose of this study was to determine the development, feasibility, effectiveness, and practicality of learning media video theme 6 subthemes 2 for grade IV students. This research is a research and development (Research and Development). The development model used is the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation,. The population in this development is 3 students, 1 teacher of class IV to find out the practicality of instructional video media developed, and there is also validation of video media from 2 expert lecturers. The results of the practicality of 3 students showed a percentage of 90.62% with a very practical category, and the results of 1 teacher showed a percentage of 92.18% with a very practical category. The results of the media validation from 2 expert lecturers showed a percentage with a very valid category.